The Naturally Occurring Host Defense Peptide, LL-37, and Its Truncated Mimetics KE-18 and KR-12 Have Selected Biocidal and Antibiofilm Activities Against Candida albicans, Staphylococcus aureus, and Escherichia coli In vitro - Luo, Yu; McLean, Denise T. F.; Linden, Gerard J.; McAuley, Danny F.; McMullan, Ronan; Lundy, Fionnuala T. (Frontiers in Microbiology, 2017)
Amongst the recognised classes of naturally occurring antimicrobials, human host defence peptides are an important group with an advantage (given their source) that they should be readily translatable to medicinal products. It is also plausible that truncated versions will display some of the biological activities of the parent peptide, with the benefit that they are less costly to synthesise using solid phase chemistry. The host defense peptide, LL-37, and two truncated mimetics, KE-18 and KR-12, were tested for their inhibitory effects and antibiofilm properties against Candida albicans, Staphylococcus aureus and Escherichia coli, microorganisms commonly implicated in biofilm-related infections such as ventilator associated pneumonia (VAP). Using in silico prediction tools, the truncated peptides KE-18 and KR-12 were selected for MIC and antibiofilm testing on the basis of their favourable cationicity, hydrophobic ratio and amphipathicity compared with the parent peptide. Two methods were analysed for determining peptide efficacy against biofilms; a crystal violet assay and an XTT (2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) assay. The biocidal activities measured by minimum inhibitory concentration (MIC) and antibiofilm activities (measured by a crystal violet assay) appeared to be independent. LL-37 had no biocidal action against C. albicans (MIC > 250 µg/ml) but significant effects in both biofilm prevention and biofilm inhibition assays. KE-18 and KR-12 yielded superior MIC values against all three microorganisms. Only KE-18 had a significant effect in the biofilm prevention assay, which persisted even at sub-MIC concentrations. Neither of the truncated peptides were active in the biofilm inhibition assay. KE-18 was shown to bind lipopolysaccharide (LPS) as effectively as LL-37 and to bind lipoteichoic acid (LTA) more effectively. None of the peptides showed haemolytic activity against human erythrocytes at the concentrations tested. KE-18 should be considered for further development as a natural peptide-derived therapeutic for prevention of multi-species biofilm-related infections such as VAP.